Cardiac Tamponade following Mitral Valve Replacement for Active Infective Endocarditis with Ring Abscess. (22nd January 2015) - Ranjan, R.; Lawrence, T.
Abstract : Periannular extension and abscess formation are rare but deadly complications of infective endocarditis (IE) with high mortality. Multimodality cardiac imaging, invasive and noninvasive, is needed to accurately define the extent of the disease. Debridement, reconstruction, and valve replacement, often performed in an emergent setting, remain the treatment of choice. Here we present a case of severe IE in a 29-year-old intravenous drug user who after undergoing debridement of the abscess, annular reconstruction, and mitral valve replacement (MVR) presented with recurrence of shortness of breath and pedal edema. Transthoracic echocardiogram (TTE) showed a6.2 × 5.5  cm cavity, posterior to and communicating with the left ventricle through a 3 cm wide fistulous opening, in proximity of the reconstructed mitral annulus. The patient underwent a redo MVR with patch closure of the fistulous opening, with good clinical outcome. This case highlights the classic TTE findings and the necessity for close follow-up in the perioperative period in patients undergoing surgery for periannular extension of infection. A cardiac magnetic resonance imaging can be considered, preoperatively, in such cases to identify the extent of myocardial involvement and surgical planning.